Direct observations of damage during unconfined brittle failure of Carrara marble. Issue 3 (20th March 2016) - Tal, Yuval; Evans, Brian; Mok, Ulrich
Abstract: To observe and quantify the production of microfracturing from initial yield to failure, we deformed Carrara marble samples in uniaxial compression at 20, 105, and 180°C and continuously observed a region of about 1 mm 2 on an exposed face with a long‐working distance microscope. Using image processing and microscale strain‐mapping techniques, we measured local strains over a length scale of tens of micrometers. By treating the images with various filters, we identified linear damage features, as well as the magnitude of localized strain and the mode of deformation, i.e., shear versus normal deformation. In general, shear deformation is more prevalent after initial yielding, while tensile deformation dominates closer to peak stress. Independent measurements of both stress and microcrack density at different stages of each experiment provide a unique opportunity to explicitly compare the data with damage models. The model of Ashby and Sammis (1990) significantly underestimated the damage that the rock could sustain before peak stress, perhaps owing to the influence of weak grain boundaries on the damage production. In these samples, microcracks tended to form near boundaries before yield stress. During strain hardening, the damage parameters increased rapidly as longer microcracks grew along the boundaries and finally transected grains as loading neared peak stress. The microcrack density can be empirically related to the reduction of Young's modulus; stiffness ratios decay exponentially with increasing microcrack density for T  ≤ 105°C. Key Points: The evolution of damage was observed continuously during failure under uniaxial loading Strain‐mapping and filtering techniques provide the mode and magnitude of deformation of microcracks Independent measurements of stress and crack density provide input to damage models